PROFIL PENALARAN SISWA SMP DENGAN KEPRIBADIAN INTROVERT DALAM MEMECAHKAN MASALAH MATEMATIKA - Fury Styo Siskawati (FKIP Universitas Islam Jember, 2015)
The purpose of the research is to describe the reasoning of the introvert students in junior high school in solving mathematical problems. The type of the research is descriptive qualitative approach. The subjects of this study were the seventh grade students in junior high school having an introvert personality. The subjects were given the task of solving the problem to know Math reasoning in solving Mathematical problems. The data collection methods used were questionnaire, interview, and test. The writer then used triangulation to minimize the writer’s subjectivity. The findings indicated that the mathematical reasoning of introvert subject in solving mathematical problems, including the process of gathering the facts related to the problem and then do the analysis, then make a conjecture and submitted arguments to reinforce the conjecture that had been filled and for which the latter is to draw conclusions and validate the conclusions that had been made. The accuracy of the subjects in terms of doing their tasks makes them to re-check the calculations they made. It is therefore, that they did not make a mistake in calculating. Then expertise in writing makes the subject gave a very long answer, full, and clear.Key Words : reasoning, problem solving, and introvert personality